MO361INCIDENCE AND RISK FACTORS OF INFECTION AFTER AN EPISODE OF ACUTE KIDNEY INJURY DURING HOSPITALIZATION. (29th May 2021) - Sanchez, Ana; Cabrera, Alicia; Salanova Villanueva, Laura; Muñoz Ramos, Patricia; Ruano, Pablo; Quiroga, Borja
Abstract: Background and Aims: Acute kidney injury (AKI) is a major risk factor for development and progression to chronic kidney disease (CKD). The aim of the present study is to assess the incidence of infections after an admission for AKI. Method: In this retrospective study all patients who developed AKI during hospitalization and were discharged from 2013 to 2014 were included. Factors associated to infections were evaluated. The mean follow-up after discharge was 39±30 months. Results: We included 1255 patients with a mean age of 75±13 years, of which 692 (55%) were men. At baseline, 944 (75%) patients presented with hypertension, 379 (30%) with diabetes, 560 (44%) with hypercholesterolemia and 543 (43%) with CKD. Mean baseline creatinine was 1, 3±1, 8 mg/dl (glomerular filtration rate [eGFR] estimated by CKD-EPI was 55±25 ml/min/1, 73m2). The peak level of creatinine reached during AKI was 2, 47±1, 97 mg/dl (eGFR 30±18 ml/min/1, 73m2). At discharge, creatinine was 1, 62 mg/dL and eGFR 53±27 ml/min/1, 73m2. Seven hundred and seventy-three (62%) patients presented an eGFR inferior to 60 ml/min/1, 73m2. During follow-up, 681(54%) patients presented an infectious event. Urinary tract infection was the most frequent infection (286 patients, 23%) followed by respiratory infection (214 patients, 17%). Factors associated with infection were age (p<0, 001), hypertension (p=0, 03), atrial fibrillation (p=0, 014), functional dependence measured by Barthel index (p=0, 03), previous diagnosis of CKD (p=0, 01), baseline eGFR (p>0, 001) and eGFR at discharge (p=0, 002). Survival analysis using Kaplan-Meier demonstrated an existing association between eGFR inferior to 60 ml/min/1, 73m2 and infections (LogRank 12, 2, p<0, 001, figure 1 ). : Adjusted multivariable analysis demonstrated that age (HR 1, 01 [CI95% 1, 00-1, 02], p=0, 009) and the presence of eGFR inferior to 60 ml/min/1, 73 m2 (HR 1, 45 [CI95% 1, 04-2, 02], p=0, 02) were independent predictors of infection after AKI episode. Conclusion: The existence of eGFR inferior to 60 ml/min/1, 73 m2 after an hospitalization with AKI shows an independent association with presenting an infection afterwards.